2010
DOI: 10.1073/pnas.1006269107
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of cortical pyramidal neurons in mice lacking high-affinity nicotinic receptors

Abstract: The neuronal nicotinic acetylcholine receptors (nAChRs) are allosteric membrane proteins involved in multiple cognitive processes, including attention, learning, and memory. The most abundant form of heterooligomeric nAChRs in the brain contains the β2-and α4-subunits and binds nicotinic agonists with high affinity. In the present study, we investigated in the mouse the consequences of the deletion of one of the nAChR components: the β2-subunit (β2 −/− ) on the microanatomy of cortical pyramidal cells. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 46 publications
8
86
0
2
Order By: Relevance
“…We showed that the balance of recurrent excitation and inhibition is disrupted in the case of awake β2 KO mice, and more specifically, the neuronal synchronicity is disrupted. It has been reported that the β2 subunit is involved in the dendritic morphogenesis of pyramidal neurons, and in particular, in the circuits that contribute to the high-order functional connectivity of the cerebral cortex (40). These defects in the maturation of the cerebral cortex that have been reported in the β2 KO mice could contribute to the observed behavioral deficits (4,13,16).…”
Section: Discussionmentioning
confidence: 95%
“…We showed that the balance of recurrent excitation and inhibition is disrupted in the case of awake β2 KO mice, and more specifically, the neuronal synchronicity is disrupted. It has been reported that the β2 subunit is involved in the dendritic morphogenesis of pyramidal neurons, and in particular, in the circuits that contribute to the high-order functional connectivity of the cerebral cortex (40). These defects in the maturation of the cerebral cortex that have been reported in the β2 KO mice could contribute to the observed behavioral deficits (4,13,16).…”
Section: Discussionmentioning
confidence: 95%
“…Although the present study focused on the semi-acute effect of nicotine within 2 h, more dramatic alterations such as spine density (Engert and Bonhoeffer 1999;Nagerl et al 2004) might be correlated to a more persistent type of plasticity. The relationship between the activity of nAChR and spine density has been recently shown; a region specific decrease in spine density is observed in b2 subunit deleted mice (Ballesteros-Yanez et al 2010;Lozada et al 2012). Notably, Lozada and colleagues have reported an acute (1 h) change in spine density in young mouse (P7) but not in older mouse (P15).…”
Section: Glutamate Mediates the Nicotine-induced Spine Remodelingmentioning
confidence: 96%
“…One way we are testing this vulnerability is by comparing the dendritic branching of pyramidal neurons in wild-type mice with animals lacking the b2-subunit of the nicotinic acetylcholine receptor (Ballesteros-Yáñez et al 2010). Loss of this subunit prevents the high-affinity binding of the neurotransmitter acetylcholine and, as a consequence, mice lacking the b2-subunit show a characteristic behavioral deficit: their exploratory drive, which is one of the most cognitive aspect of mouse behavior, is reduced, although their navigation abilities, a more automatic activity, are unaffected.…”
Section: Epigenetics and Higher Brain Functionmentioning
confidence: 99%